STRATEGY FOR STRENGTHENING SUSTAINABLE BUMDESA IN PAMIJAHAN BOGOR: A PESTLE ANALYSIS APPROACH - Ade Wahyudi; Iha Haryani Hatta; Dewi Trirahayu (Jurnal Ekonomi, 2023)
This study analyzes strategies for strengthening sustainable Village-Owned Enterprises (BUMDesa) in Pamijahan District, Bogor Regency. The PESTLE (Political, Economic, Social, Technological, Legal, and Ecological) analysis approach is used to identify environmental factors that influence BUMDesa sustainability and their impact on achieving Sustainable Development Goals (SDGs). The type of research used is Descriptive Research of the Conclusive Research type. This study's primary data was obtained through a survey method by distributing online questionnaires to the community involved in BUMDesa. Secondary data is used as supporting data and information for researchers. The research population was the BUMDesa community in Pamijahan District, Bogor, using a non-probability sampling technique of the snowball sampling type. The study results show that the PESTLE analysis significantly affects the sustainability of BUMDesa and its impact on the SDGs. Good BUMDesa management can increase equitable economic growth (SDGs 8) and encourage village infrastructure and innovation (SDGs 9). Collaboration with related parties, developing innovations in developing village economic activities, and attention to maintaining cultural and natural heritage is essential in achieving this goal. Based on the research results, BUMDesa administrators must continue encouraging village community members' active participation in decision-making and management. Collaboration with local government, financial institutions, and NGOs can strengthen the village's economic development. Supporting innovation in developing village economic activities needs to be continuously improved. Cultural and natural heritage maintenance must also be a significant concern in BUMDesa development.